Sensitivity analysis on PROMETHEE and TOPSIS weights - (:unkn) unknown (Inderscience Publishers, 2014)
The purpose of this paper is to determine the changes of the outrankings of alternatives due to the changes of weights. It is analysed that the altering of weights of PROMETHEE is how affecting the outrankings by using stability intervals. It is also tested that when the changes of weights in PROMETHEE are applied to TOPSIS weights at the same level, how the TOPSIS outranking alters. Weights are subjective factors in multi criteria decision making methods for that reason they vary in determination. When you change the weights, the outrankings of the methods alter. It will be interesting to discuss in this paper how the influence they have on the outrankings of the methods. Sensitivity analysis is performed over PROMETHEE and TOPSIS weights by using stability intervals. In this study the main focus will be stability intervals of weights and the altering of outrankings due to changing of weights. Stability intervals allow seeing at a glance in which ranges the weights of the different criteria could move without affecting the best solution. © 2014 Inderscience Enterprises Ltd.
Keywords: MCDM; Multi criteria decision making; PROMETHEE; Sensitivity analysis; TOPSIS